Biomaterial Based Approaches to Study the Tumour Microenvironment - Winter, Jessica (Chemical engineer); Rao, Shreyas (Biomaterials science series., 2022)
This book provides an introduction to the rich chemical, topographical, and mechanical cues in the tumour microenvironment and then introduces readers to bioengineering strategies.